Pan-Resistance; A Rising Challenge in Burns Patients - Amir Taimur Khan, Hamza Khan Shahbazi, Saddaf Imran, Syed Muhammad Haider, Ekram Ud Din, Shandanah, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Burn injuries by fire and hot liquids and contact with hot surfaces have been recognized as a significant and major public health problem in economically developing countries. Objectives: The main objective of the study is to find the incidence of pan-resistant strain infections, in burns Khyber teaching hospital, Peshawar. Material and methods: A retrospective observational study was conducted to determine the incidence of pan-resistant strain infections in burn patients at Khyber Teaching Hospital, Peshawar. The study was conducted over a period of 12 months, from January 1, 2022, to December 31, 2022. Khyber Teaching Hospital is a tertiary care hospital located in Peshawar, the capital city of Khyber Pakhtunkhwa province in Pakistan. Results: Table 1 presents the demographic and clinical characteristics of the study population. The table shows that the study included 100 patients with burn injuries, with a mean age of 28.5 years (SD 14.7). The majority of patients were male (70.0%) and had burn injuries covering more than 10% of their total body surface area (78.0%). The most common cause of burn injury was flame (52.0%). The mean length of hospital stay was 15.4 days. Practical Implication: This study implies and plays a role in finding the proper antibiotics which will be used for burn wounds. Conclusion: The study concludes that a significant proportion of bacterial isolates obtained from burn wound cultures were resistant to multiple antibiotics, with Acinetobacter baumannii showing a pan-resistant pattern. Keywords: Significant, Acinetobacter, Surface, Resistance, Clinical, Wound